THE EFFECT OF CBRT GOVERNOR CHANGES ON THE BORSA ISTANBUL BANKİNG INDEX (Third Sector Social Economic Review, 2024)
The Central Bank of the Republic of Turkey (CBRT) is an independent administrative authority that derives its powers from the law. Since the implementation of the presidential government system on July 9, 2018, five CBRT governors have been replaced. None of the departing governors completed their legal terms. Announcements regarding the replacement of CBRT governors before the end of their terms are expected to affect financial markets. This study aims to examine the impact of these announcements on the returns of stocks traded on the stock exchange. The decisions made by CBRT governors inevitably affect all sectors. However, since the banking sector is expected to be directly affected, the study focuses on the stocks of banks listed in the Borsa Istanbul banking index. The event study method was used in this study. The event dates were considered as the first trading days in the markets following the changes in CBRT governors. The results indicate that investor reactions to CBRT governor changes in the banking index stocks varied. While some bank stock prices reacted positively to these announcements, others reacted negatively. However, the reactions of investors in Akbank, Garanti Bank, İş Bank, and Yapı ve Kredi Bank were found to be consistent. No consistency was observed in the reactions of other banks' shareholders.
Keywords: CBRT; CBRT Governors; Borsa Istanbul; Banking Index; Event Study